Gender-Based Violence in Post-Earthquake Disaster Situations in Central Sulawesi - Sultan, Soraya; Muhamad, Hasan; Hatta, Ikhtiar (UIN Sunan Gunung Djati, 2026)
Women and children are vulnerable to gender-based violence (GBV) rooted in patriarchal culture and spatial injustice against women and children. This study aims to explain the forms of GBV experienced by women and children in emergency situations and post-earthquake disasters in Donggala Regency, Central Sulawesi. This study uses a qualitative approach with in-depth interviews with survivors, volunteers, and victim advocates. Data are analyzed thematically with a feminist perspective to understand the power relations and social structures that influence GBV. The study found four main forms of GBV, namely: (1) sexual violence consisting of rape including incest, peeping, and forced kissing; (2) physical violence, namely beatings and physical aggression; (3) psychological violence, namely intimidation, stigma, and ostracism; and (4) economic violence, namely neglect of wives and children, forced work, and shifting gender roles. It is concluded that sexual violence is the most dominant form and has serious impacts, such as prolonged trauma and the loss of educational opportunities for victims. The post-disaster situation exacerbates the vulnerability of women and children as objects of violence. These findings recommend gender-sensitive disaster management policies, the provision of safe spaces, and strengthening legal protection mechanisms to prevent and address GBV in crisis situations.